NAVIGATION, CONSCIOUSNESS AND THE BODY/MIND »PROBLEM«*) - M.J. Cotterill, Rodney (Psyke & Logos, 2022)
Exploitation of an unconscious veto mechanism, mediated by a specific cortical circuit, and made possible by an adequate very-short-term memory span, paradoxically requires conscious awareness. Part of the same circuit, interacting with other brain components, permits internal simulations of the body’s interactions with the environment, thereby providing the basis of mind. *) Presented on 21 August 1997 at the Brain & Self Workshop, Helsingør, Denmark.